Comparison of Perioperative Outcomes of Total Laparoscopic and Robotically Assisted Hysterectomy for Benign Pathology during Introduction of a Robotic Program - Gokhan Sami Kilic; Gradie Moore; Ayman Elbatanony; Carmen Radecki; John Y. Phelps; Mostafa A. Borahay (Obstetrics and Gynecology International)
Study Objective. Prospectively compare outcomes of robotically assisted and laparoscopic hysterectomy in the process of implementing a new robotic program. Design. Prospectively comparative observational nonrandomized study. Design Classification. II-1. Setting. Tertiary caregiver university hospital. Patients. Data collected consecutively 24 months, 34 patients underwent laparoscopic hysterectomy, 25 patients underwent robotic hysterectomy, and 11 patients underwent vaginal hysterectomy at our institution. Interventions. Outcomes of robotically assisted, laparoscopic, and vaginal complex hysterectomies performed by a single surgeon for noncancerous indications. Measurements and Main Results. Operative times were 208.3±59.01 minutes for laparoscopic, 286.2±82.87 minutes for robotic, and 163.5±61.89 minutes for vaginal (𝑃<.0001). Estimated blood loss for patients undergoing laparoscopic surgery was 242.7±211.37 cc, 137.4±107.50 cc for robotic surgery, and 243.2±127.52 cc for vaginal surgery (𝑃=0.05). The mean length of stay ranged from 1.8 to 2.3 days for the 3 methods. Association was significant for uterine weight (𝑃=0.0043) among surgery methods. Conclusion. Robotically assisted hysterectomy is feasible with low morbidity, a shorter hospital stay, and less blood loss. This suggests that robotic assistance facilitates a minimally invasive approach for patients with larger uterine size even during implementing a new robotic program.